2023
DOI: 10.1080/20008066.2023.2211355
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial resources underlying disaster survivors’ posttraumatic stress symptom trajectories: insight from in-depth interviews with mothers who survived Hurricane Katrina

Abstract: Background : Weather-related disasters, including hurricanes, are becoming more frequent and severe due to climate change. Vulnerable populations, such as people with low income and racial and ethnic minorities, are particularly prone to increased levels of physical harm and psychiatric adversity from weather-related events. Objectives : We aimed to explore psychosocial resources and coping of survivors with three different posttraumatic stress symptom (PTSS) trajectories ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…While social support had a buffering effect, this effect was not seen for those with a high stress load. It is also well demonstrated that there are demographic disparities that moderate the health effects of climate change (Benevolenza & DeRigne, 2019 ), particularly among vulnerable populations such as low-income individuals (Tekin et al, 2023 ) and racial and ethnic minorities (Berberian et al, 2022 ). Pertinently, in addition to individual pre-existing vulnerabilities, the financial stressors emerging directly from extreme disaster events are a core mediator between these events and their adverse mental health outcomes.…”
Section: Moderators and Mediators Of Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…While social support had a buffering effect, this effect was not seen for those with a high stress load. It is also well demonstrated that there are demographic disparities that moderate the health effects of climate change (Benevolenza & DeRigne, 2019 ), particularly among vulnerable populations such as low-income individuals (Tekin et al, 2023 ) and racial and ethnic minorities (Berberian et al, 2022 ). Pertinently, in addition to individual pre-existing vulnerabilities, the financial stressors emerging directly from extreme disaster events are a core mediator between these events and their adverse mental health outcomes.…”
Section: Moderators and Mediators Of Vulnerabilitymentioning
confidence: 99%
“…Similarly, Liu et al ( 2021 ) found greater social support increases self-compassion and posttraumatic growth in the aftermath of trauma; as well as increasing prosocial and reducing antisocial behaviours. Individual-level psychosocial resources are also critical protective factors against negative mental health outcomes, with Tekin et al ( 2023 ) finding that in survivors of Hurricane Katrina, factors such as hope for the future, efficient coping strategies, and acceptance of the situation were associated with recovery trajectories of posttraumatic stress, reflected in improvements in individuals’ symptoms over time. While the cumulative impacts of climate change are severe, this evidence points to a number of individual- and community-level protective factors which may buffer the negative mental health effects of climate change-related disaster events and lasting environmental changes.…”
Section: Resilience and Protective Factorsmentioning
confidence: 99%